Assessment of the Impact of Floods to the Local Community in Nyarusiza Sub-County Kisoro District. - Murengezi, Innocent (Kabale University, 2024)
The study investigated the impact of floods on the local communities and developed policy options not only to mitigate flooding in communities of Kisoro District but also Uganda at large Nyarusiza Sub-county, Kisoro District. Specific Objectives included; identifying the causes of floods, identifying the impacts of floods on communities, and identifying the solutions to floods on communities in the Nyarusiza Sub-county, Kisoro District. The researcher used the descriptive research design as appropriate for the study because the study was concerned with finding answers to research questions about the study. The Population of this study comprised farmers and communities from the Nyarusiza sub-county whose property has been destroyed due to floods especially those in some parishes like Rukongi, Mabungo, and Gasovu who were 239 in number. The researcher used the Krejcie and Morgan table to determine the 148 who represented the whole study population. Data collection methods and tools used to collect data included questionnaires and interview guides. Descriptive analysis is used to determine the proportions and frequency of the variables. The results were presented in the form of tables and figures. The findings of the study on objective one revealed that the main cause of floods in communities is due to Heavy Rainfall. During this time, rainwater flows and is collected in dams. When this tired or collected water reaches beyond the storage capacity limit, it ends up in flood. Floods caused by rainfall usually occur at the flat areas in Nyarusiza sub-county plains causing flooding hence this accounted for 25(17%) of the respondents. The findings on the second objective revealed that the spread of Communicable Diseases is the main effect of waterborne diseases like cholera, typhoid fever, hepatitis, and leptospirosis in flood-affected areas. Floods also lead to vector-borne diseases, transmitted through parasites and pathogens such as mosquitoes. As a result, the health of flood, victims deteriorates as this accounted for 25(17%). The findings on objective three revealed that there is a need for a risk Assessment Plan hence creating a risk assessment plan should be a top priority when it comes to your business. Consider what needs to happen if there is flooding and get a plan of action in case employees are unable to make it to work. To prepare for a flood, consider an evacuation plan, as well as what items, materials, and equipment might be at risk, and how to best keep them safe during a flooding disaster. This accounted for 13(9%) of the respondents. The researcher concludes that the different coping mechanisms to seasonal floods adopted by people include among other considerations: the construction of flood protection embankments, the creation of water drainage canals, and maintaining hygiene.